2016
DOI: 10.1038/srep32817
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and phylogeny of Cambrian ecdysozoans tested by experimental decay of Priapulus

Abstract: The exceptionally preserved Cambrian fossil record provides unique insight into the early evolutionary history of animals. Understanding of the mechanisms of exceptional soft tissue preservation frames all interpretations of the fauna and its evolutionary significance. This is especially true for recent interpretations of preserved nervous tissues in fossil ecdysozoans. However, models of soft tissue preservation lack empirical support from actualistic studies. Here experimental decay of the priapulid Priapulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 56 publications
(139 reference statements)
1
57
0
Order By: Relevance
“…Notable examples are the jaws and chaetae of nereid polychaetes, [48] the notochord and myomeres of chordates, [20] and the chitinous parts of non-arthropod ecdysozoans such as the claws of onychophorans [17] and scalids of priapulids. [18] Despite the apparent decay resistance of these structures, however, they are not always preserved in fossils. The jaws of nereid polychaetes, for example, do not survive diagenesis despite being heavily sclerotized: they only survive in recent sediments, [61] whereas the jaws of other polychaetes occur abundantly as fossils.…”
Section: Boxmentioning
confidence: 99%
See 4 more Smart Citations
“…Notable examples are the jaws and chaetae of nereid polychaetes, [48] the notochord and myomeres of chordates, [20] and the chitinous parts of non-arthropod ecdysozoans such as the claws of onychophorans [17] and scalids of priapulids. [18] Despite the apparent decay resistance of these structures, however, they are not always preserved in fossils. The jaws of nereid polychaetes, for example, do not survive diagenesis despite being heavily sclerotized: they only survive in recent sediments, [61] whereas the jaws of other polychaetes occur abundantly as fossils.…”
Section: Boxmentioning
confidence: 99%
“…[51] The same decay experiments allowed the chevron-shaped structures in Conopiscius, a Carboniferous chordate, to be interpreted as myomeres rather than external scales, and also indicated that a decay-resistant cuticle was not necessarily present in Pikaia from the Burgess Shale. [51,55] Decay in seawater has now been monitored in a range of taxa in laboratory experiments (see Table S1, Supporting Information): anthozoans, [56] annelids, [48] chaetognaths, [57] priapulids, [18] onychophorans, [17] pterobranchs, [58] enteropneusts, [59] nonvertebrate chordates, [20] and cyclostomes. [60] Thus the sequence of character loss has been determined for taxa representing most clades of eumetazoans.…”
Section: Boxmentioning
confidence: 99%
See 3 more Smart Citations